Distinct spatial maps and multiple object codes in the lateral entorhinal cortex - Huang, Xu; Schlesiger, Magdalene; Barriuso-Ortega, Isabel; Leibold, Christian; MacLaren, Duncan Archibald Allan; Bieber, Nina; Monyer, Hannah (Neuron, 2023)
The lateral entorhinal cortex (LEC) is a major cortical input area to the hippocampus, and it is crucial for associative object-place-context memories. An unresolved question is whether these associations are performed exclusively in the hippocampus or also upstream of it. Anatomical evidence suggests that the LEC processes both object and spatial information. We describe here a gradient of spatial selectivity along the antero-posterior axis of the LEC. We demonstrate that the LEC generates distinct spatial maps for different contexts that are independent of object coding and vice versa, thus providing evidence for pure spatial and pure object codes upstream of the hippocampus. While space and object coding occur by and large separately in the LEC, we identified neurons that encode for space and objects conjunctively. Together, these findings point to a scenario in which the LEC sustains both distinct space and object coding and associative space-object coding.
Online verfügbar: 20. Juli 2023, Dokumentversion: 4. Oktober 2023
Gesehen am 26.01.2024